The E-Learning Design for Problem Based Learning in Dynamic Fluid Topic using Microsoft Sway - Prihartini Khoirun Nissa; Benedikta Lorenza Dheanti (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2021)
The development of information and communication technology (ICT) based on education can be an opportunity to improve the learning process. Learning in the pandemic era Covid-19 needs media that help teachers and students enthusiasm for learning. The lessons with e-learning are flexible and easy to use. Microsoft Sway 365 is one of the e-learning that can be used because of the features such as presentation, text, images, video, and sound. This study aims to produce e-learning using Microsoft Sway on Dynamic Fluid. This study uses an R&D method with the 4D model but only defines, designs, and develops stages. Media experts and material experts validated the e-learning. The validity test result from content experts showed that the e-learning using sway was feasible with 77.7% and from media experts was feasible with 77.5%. The study concludes that e-learning with Microsoft Sway is flexible, easy to use, can support physics learning with fun, and feasible to be used as a teaching medium that helps students in explanatory activities.